The invisible economy and gender inequalities : the importance of measuring and valuing unpaid work. - Pan American Health Organization (Washington, D.C. : Pan American Health Organization, 2010)
"La salud y el cuidado infantil no remunerados proporcionados en el hogar, junto con otras actividades que contribuyen al desarrollo físico, cognitivo y emocional de los miembros de un hogar, tienen un impacto importante en el bienestar individual y público, así como en el desarrollo humano potencial de los países. Estas actividades económicas, realizadas en gran medida por mujeres, se llevan a cabo fuera del mercado y, por lo tanto, son invisibles en las estadísticas económicas y los sistemas de cuentas nacionales de la mayoría de los países. En realidad, la invisibilidad del trabajo no remunerado de las mujeres en la prestación de servicios de salud a otros miembros del hogar y de la comunidad, y en el desarrollo del capital humano de las nuevas generaciones, impide un análisis adecuado del impacto de las políticas públicas sobre ellas y dificulta una definición de estrategias más amplias de desarrollo económico y social. Los capítulos de este volumen presentan aspectos conceptuales, metodológicos y empíricos relacionados con la medición y valoración del tiempo dedicado por los miembros del hogar a actividades productivas no de mercado, que son invisibles en los sistemas de cuentas nacionales regidos por el Sistema de Cuentas Nacionales de 1993 ( SNA, 1993). La mayoría de los capítulos fueron preparados por la Organización Panamericana de la Salud en colaboración con la Comisión Económica para América Latina y el Caribe y el Consejo Nacional de Investigaciones Científicas de España entre 2001 y 2006." (Copiado del prologo).
Acknowledgments. Prologue. Introduction. Parte I: Household satellite accounts and the measurment and valuation of unpaid work: results and policy implications for the reduction of gender inequalities. Chapter 1. The valuation of unpaid work: a key strategy for gender equality policy. Chapter 2. Household production accounts for Canada, Mexico, and the United States: methodological issues, results, and recomendations. Chapter 3. Satellite account for unpaid household services: an approximation for Mexico. Chapter 4. Calculating the value of unpaid labor. Chapter 5. Conceptual framework and methodological guidelines for the household satellite account to measure unpaid work in health. Chapter 6. The inclusion of unpaid work in the analyses of the health and social welfare sectors. Ten good reasons for measuring unremunerated work in health care. Part II: Conceptual and methodological challenges. Chapter 7. Time use surveys: desing and application. Chapter 8. Methodological proposal to measure and assess unpaid household health care. Chapter 9. The invisible costs of caring for patients in the household: a chilean case study. Chapter 10. Women, working, and caring in this Millennium. Chapter 11. Defining and valuing child care: lessons from time use surveys in major english-speaking countries. Parte III: Experiences and results. Chapter 12. Time and work from a feminine perspective. Chapter 13. Policy and strategy in health care provision in the PAHO region, and measuring unpaid work.
Keywords: .